2010
DOI: 10.2298/vsp1002136s
|View full text |Cite
|
Sign up to set email alerts
|

Fasciocutaneous flaps of the lower leg: Anatomic study and clinical significance

Abstract: Septocutaneous perforator systems of the lower leg have constant and reliable pattern of existance. Lower leg length was 36 cm in average, (between 33 and 43 cm). Lower leg was divided in 10 equal segments, 3.6 cm each. A. tibialis posterior and a. peronea had 5 septocutaneous perforators. Cluster analysis of a. tibialis posterior perforators (with diameter > or = 0.5 mm), discovered 5 reliable levels of septocutaneous perforators. These levels are at 3.6-10.8 cm; 14.4--21.6 cm and 25.2-28.8 cm. For a. peronea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As the main blood supply to the lower leg, the posterior tibial artery sent a mean of 2 to 7 perforating/cutaneous branches along the line, joining the tibial tuberosity and the medial malleolus. Stevanović et al 16 found that these septocutaneous perforators were mainly found at levels of 3.6 to 10.8 cm, 14.4 to 21.6 cm, and 25.2 to 28.8 cm from the tip of the medial malleolus. Nenad 12 et al confirmed that > 90% of the perforating branch of the posterior tibial artery was of solid caliber.…”
Section: Discussionmentioning
confidence: 99%
“…As the main blood supply to the lower leg, the posterior tibial artery sent a mean of 2 to 7 perforating/cutaneous branches along the line, joining the tibial tuberosity and the medial malleolus. Stevanović et al 16 found that these septocutaneous perforators were mainly found at levels of 3.6 to 10.8 cm, 14.4 to 21.6 cm, and 25.2 to 28.8 cm from the tip of the medial malleolus. Nenad 12 et al confirmed that > 90% of the perforating branch of the posterior tibial artery was of solid caliber.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular axis of the posterior tibial artery lies along a line which is ~4.5 cm medial and parallel to the line which joins the tibial tuberosity and the midmalleolar point [32]. The septocutaneous perforators which arise from it are arranged in three clusters, the most proximal of which is 3.6-10.8 cm below the joint line [33]. The peroneal artery perforators [34] are situated along an oblique line, behind the posterior border of the fibula, along the intermuscular septum, between the soleus and the peroneus longus.…”
Section: Discussionmentioning
confidence: 99%